Comparative mortality outcomes in metabolic dysfunction-associated steatotic liver disease and nonalcoholic fatty liver disease subtypes in the United States - Pengwei Zhang; Sijia Yang; Rong Hu; Tianfang Peng; Peipei Yu; Yijun Zeng; Chunhong Ye; Panpan Wang; Xianhui Dong; Zhiying Che (PLoS ONE, 2025)
Background In 2023, experts from the European and American regions proposed the concepts of steatotic liver disease (SLD) and metabolic dysfunction-associated steatotic liver disease (MASLD). MASLD was proposed as a replacement for nonalcoholic fatty liver disease (NAFLD). We compared the long-term outcomes of patients with MASLD, NAFLD, and various subtypes of SLD. Methods We conducted a retrospective study using the NHANESIII database. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for all-cause mortality and cause-specific mortality among patients with subtypes of SLD, MASLD, and NAFLD. Results During a follow-up period of 31 years (median 25 years), the adjusted risks of all-cause death for patients with MASLD was 1.19 (95% CI 1.06–1.34; P = 0.006) vs . the non-SLD group. There was a moderate level of consistency between MASLD and NAFLD (Cohen’s kappa coefficient of 0.62545). Advanced fibrosis was the most serious risk factor for all-cause mortality in MASLD, and high C-reactive protein concentration was the most serious risk factor for all-cause mortality in NAFLD, followed by type 2 diabetes. Conclusions MASLD is associated with a higher risk of all-cause mortality, and this association is independent of patients’ demographic or metabolic characteristics, despite a relatively small hazard ratio. Our research findings further support that MASLD is a pathological disease related to liver disease itself. Therefore, redefining NAFLD as MASLD may help improve our understanding of predictive factors that increase the risk of death.